Reduction of MTT by Glutathione S-Transferase - J.L. York; L.C. Maddox; P. Zimniak; T.E. McHugh; D.F. Grant (BioTechniques)
The reduction of the tetrazolium salt 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) to a blue formazan product is widely used for assaying cell survival and proliferation. The reduction reaction is catalyzed by dehydrogenases localized in the mitochondria of viable cells. As part of an analysis of the ability of glutathione S-transferase (GST) enzymes to protect cells from electrophilic compounds, we found extremely high background levels of the formazan product produced by cells that overexpressed the mouse GST P1-1 enzyme. Further analysis with purified GST enzymes confirmed the ability of these enzymes to reduce MTT in vitro. These data suggest that cytotoxicity assays using MTT should be interpreted with caution, especially when studying the effects of compounds that can influence GST expression.